Interactivity of Security Topics on Social Media Pages: An Analytical Study - Bawi, Mahmoud Ali; Al-Rubaye, Bairq Hussein Jumaah (ALBAHITH ALALAMI, 2025)
This research aims to examine the interactivity of security topics published on social media pages—specifically focusing on the program "Call Number One"—in enhancing public awareness through its reported content. The study also seeks to identify the persuasion and awareness strategies employed in the program and to answer the primary research question: “What is the relationship between following security programs and audience interactivity on television’s social media pages?” The researcher adopted a survey method, typical of descriptive research, and utilized content analysis to gauge audience interactivity with the "Call Number One" program via the Facebook page of the Al Rabiaa Satellite Channel. The technical dimensions of interactivity were delineated according to six fundamental criteria: the plurality of options, the effort invested in accessing information, responsiveness to the audience, facilitation of personal communication, ease of adding information, and the implementation of a monitoring system. The findings revealed that the "Call Number One" program comprehensively employed persuasive techniques in the analysed episodes while consistently adopting an awareness approach across all topics. Moreover, the results indicated a heightened level of audience interactivity on Facebook, reflecting a strong public interest in security issues that impact their social lives, as measured by the interactivity scale used in the study.